Photocatalytic and Photoluminescence studies of ZnO nanomaterials by Banana peel powder. (2017) - Arun kumar, N.B.; Sirajudeen, J.; Nagaswarupa, H.P.; Anil Kumar, M.R.; Ravi Kumar, C.R.; Gurushantha, K.; Shashi Shekhar, T.R.; Anantharaju, K.S.; Vishnu Mahesh, K.R.; Sharma, S.C.; Nagabhushana, H.
Abstract: ZnO nanomaterials (ZNPs) were synthesized by a green mediated solution combustion method by using banana peel. The obtained products were well characterized by PXRD, FTIR, DRS and SEM. All the diffraction peaks were matched with hexagonal phase, Wurtzite structure (JCPDS card No. 89-1397 with space bunch P63mc, No.186) of ZnO. The crystallite size calculated from Scherer's formula was found to be in the range 30-50 nm. SEM images clearly reveal that irregular, pours and agglomerated morphologies. The optical band gap decreases from 3.41 to 3.26 eV when the sample was calcined at 800 °C and was confirmed by DRS. The PL properties of ZnO under 383 nm excitation was studied in order to investigate the possibility of its use in display applications. Further, the influence of ZnO material was investigated for the PC degradation of Rhodamine-B.